Lives intertwined by social invisibility: the formation of the teaching identity in the context of socio-education (Research, Society and Development, 2021)
This qualitative study presents the life trajectories of teachers who teach teenagers who commit criminal acts, who are in compliance with a socio-educational measure of hospitalization at the Foundation Center for Socio-educational Assistance to Adolescents - FCASA, the institution responsible for the socio-educational execution in a closed environment in the State of São Paulo, to point out how experiences influence the constitution of the teaching identity and reverberate in the teaching activities and in the life projects of adolescents. The method used was the Oral History of Life of twelve teachers who teach in three Internment Centers. The method was crucial to understand how their stories, challenges and achievements collaborate for teenagers to tread paths, with the reference of someone who went through similar situations and abandoned the condition of being socially oppressed. The article presents some Gordian knots of education and emerges the condition for the effectiveness of public policies, in the in-depth treatment of Human Rights.